Embodied learning made visible through line drawing: Examples from sloyd education - Jagell, Elisabet (Formakademisk, 2023)
Visual material in the form of video, still images or drawings can show parts of embodied learning that text cannot. Research ethics requirements pose a challenge in terms of making younger students’ multimodal learning visible, as the informants need to be anonymized, and this raises the challenge of how important information, such as gaze and facial expressions, can be shown. The ethical requirements exist to protect underage students, and to contribute with a scientific basis for teaching, practical and feasible methods are needed in which the students’ communication can be illustrated while ensuring their protection.  This paper explores how empirical data from studies involving younger students can be presented so that learning can be visualized while respecting ethical guidelines. The reasoning regarding the methods presented in the paper can also be useful overall for the anonymization of visual ethnography studies, in which the interest is to present empirical data from video recordings so that embodied learning can be made visible.